Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41598-022-08085-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations between classic psychedelics and opioid use disorder in a nationally-representative U.S. adult sample

Abstract: Opioid use disorder (OUD) is a major source of morbidity and mortality in the U.S. and there is a pressing need to identify additional treatments for the disorder. Classic psychedelics (psilocybin, peyote, mescaline, LSD) have been linked to the alleviation of various substance use disorders and may hold promise as potential treatments for OUD. The aim of this study was to assess whether the aforementioned classic psychedelic substances conferred lowered odds of OUD. Furthermore, this study aimed to replicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
(29 reference statements)
0
19
0
1
Order By: Relevance
“…In this study, however, the possibility that pre-drug differences explain the differing associations between racial and ethnic groups is a key takeaway and invites further investigation into the characteristics of racial and ethnic minorities who use psychedelic drugs. Furthermore, other population-based survey research has found suggestive evidence that third-variable sociodemographic differences (e.g., socioeconomic status, education) may underlie the associations between naturalistic psychedelic use and lowered odds of mental health disorders as well 34 , 35 . Therefore, third-variable demographic differences between White and racial and ethnic minority participants may explain why protective associations between psychedelic use and distress and suicidality were found only for White participants.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, however, the possibility that pre-drug differences explain the differing associations between racial and ethnic groups is a key takeaway and invites further investigation into the characteristics of racial and ethnic minorities who use psychedelic drugs. Furthermore, other population-based survey research has found suggestive evidence that third-variable sociodemographic differences (e.g., socioeconomic status, education) may underlie the associations between naturalistic psychedelic use and lowered odds of mental health disorders as well 34 , 35 . Therefore, third-variable demographic differences between White and racial and ethnic minority participants may explain why protective associations between psychedelic use and distress and suicidality were found only for White participants.…”
Section: Discussionmentioning
confidence: 97%
“…These covariates not only mirror those from Simonsson et al (2021a, 2021b, 2021c), which we sought to replicate and extend, but also broadly match those from other population-based survey research on classic psychedelics (Hendricks et al, 2015, 2018; Jones, Lipson, et al, 2022; Jones, Ricard, et al, 2022; Jones and Nock, 2022a, 2022b, 2022c, 2022d). Furthermore, these variables control for a wide range of potentially confounding sociodemographic and substance use factors known to influence health outcomes (Christensen et al, 2018; Hu et al, 2017; Inoue-Choi, McNeel, et al, 2019; Inoue-Choi, Shiels, et al, 2019; Levola et al, 2020).…”
Section: Methodsmentioning
confidence: 86%
“…Both lifetime classic psychedelic use and sick leave have been associated with certain sociodemographic characteristics and use of other substances [ 11 , 38 , 44 , 48 , 49 ]. We therefore controlled for: age, gender, ethnoracial identity, educational level, annual household income, marital status, risky behavior (i.e., “Like to test yourself by doing risky things”), lifetime use of cocaine, other stimulants, sedatives, tranquilizers, heroin, pain relievers, marijuana, phencyclidine (PCP), 3,4-methylenedioxymethamphetamine (MDMA/ecstasy), inhalants, smokeless tobacco, pipe, cigar, and daily cigarettes, as well as age of first alcohol use.…”
Section: Methodsmentioning
confidence: 99%
“…Findings from clinical research on classic psychedelics are supported by results from cross-sectional studies with nationally representative samples [ 37 , 38 , 39 , 40 ], but more recent cross-sectional research has also found associations between lifetime classic psychedelic use and lower odds of obesity and cardiometabolic diseases in the past year [ 41 , 42 , 43 ]. While causality has not been established, such findings could potentially be explained by healthy lifestyle changes after classic psychedelic use [ 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 97%